Evaluasi Program Penerimaan Mahasiswa Baru di Instansi Pendidikan dengan Pendekatan Sosialisasi - Gulo, Sari Pratama; Pasmah, Al Fasyah; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the evaluation of the new student admission program with a socialization approach. Socialization is a way to promote the organization directly. The goal is to describe socialization in new student admissions in educational institutions that can explain the context, input, process, and products that exist in the university environment. So that it can see the evaluation of the public relations program carried out. This research is a literature study to understand and study theories from various literatures relevant to the research. This literature technique uses content analysis as a data analysis technique. The evaluation carried out looks at the socialization that describes the background through the context, the evaluation that assesses the existing indicators through inputs, resources, facilities and infrastructure to achieve program goals, the evaluation process is carried out by SNMPTN, SBMPTN, and Independent pathways, while product evaluation is carried out by assessing the suitability of campus capacity.